RESPON PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH KERITING AKIBAT PEMBERIAN PGPR DAN PUPUK SP-36 - Fahrozy Guntoro; Syamsul Bahri; Adnan (Jurnal Cakrawala Ilmiah, 2023)
Growth and Yield Responses of Curly Red Chili Plants Due to PGPR and Sp-36 Fertilizers. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Samudra University, with an altitude of ± 10 meters above sea level. The method used in this study was the RBD (Randomized Block Design). The research was carried out for 3 months starting from October 2022 to January 2023 and had 2 factors, namely PGPR and Fertilizer SP-36. The aplication of consisted of: 20 ml/l air (D1),25 ml/l air (D2) and 30 ml/l air (D3). While SP-36 fertilizer application consists of 3 sub factors, namely: 100 kg/ha (P1), 200 kg/ha (P2) and 300 kg/ha (P3). The results showed that the PGPR dose treatment increased theplant height at 4 WAP, number of branches at 7 WAP, and fruit production per hectar. However decreased at 2 WAP plant height, number of branches 5 MST stem diameter, fruit length and plant weight per sample. The best results were obtained at the 25 ml/l PGPR dose. The results showed that the treatment with SP-36 fertilizer increased the plant height at 4 WAP. The best results were obtained in the P3 treatment of SP- 36 fertilizer 300 kg/ha. The interaction between PGPR Dosage treatment and SP-36 fertilizer increased to the parameter number of branches 7 WAP The best interaction results in the administration of PGPR doses and SP-36 fertilizer were PGPR doses of 25 ml/l and SP-36 fertilizers of 300 kg/ha.